2015
DOI: 10.2337/db15-0699
|View full text |Cite
|
Sign up to set email alerts
|

Asna1/TRC40 Controls β-Cell Function and Endoplasmic Reticulum Homeostasis by Ensuring Retrograde Transport

Abstract: Type 2 diabetes (T2D) is characterized by insulin resistance and β-cell failure. Insulin resistance per se, however, does not provoke overt diabetes as long as compensatory β-cell function is maintained. The increased demand for insulin stresses the β-cell endoplasmic reticulum (ER) and secretory pathway, and ER stress is associated with β-cell failure in T2D. The tail recognition complex (TRC) pathway, including Asna1/TRC40, is implicated in the maintenance of endomembrane trafficking and ER homeostasis. To g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
52
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(59 citation statements)
references
References 44 publications
(52 reference statements)
7
52
0
Order By: Relevance
“…4a,b). These strong general effects on the integrity of the liver support previous observations of the essential functions of TRC40 pathway in development and tissue homeostasis212223252930. In contrast to enzymatic activities indicating liver damage, the serological levels of cholesterol and triglycerides in Cre-positive animals did not change significantly in comparison to control littermates (Supplementary Fig.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…4a,b). These strong general effects on the integrity of the liver support previous observations of the essential functions of TRC40 pathway in development and tissue homeostasis212223252930. In contrast to enzymatic activities indicating liver damage, the serological levels of cholesterol and triglycerides in Cre-positive animals did not change significantly in comparison to control littermates (Supplementary Fig.…”
Section: Resultssupporting
confidence: 88%
“…Generation of conditional knockouts restricted to specific cell types allows the identification of relevant functions of components of the TRC40 pathway in tissue development and physiology. A recent study revealed that pancreatic beta cells lacking TRC40 show impaired insulin secretion23, whereas CAML is required for thymocyte development24, and loss of either receptor subunit in inner ear cells causes deafness2526.…”
mentioning
confidence: 99%
“…Taken together, our findings indicate feedback control, where loss of AtGET function and the resulting failure of SYP123 protein insertion activate inhibition at the transcript level to decrease steady-state levels of both mRNA and protein. Functional cross-talk between the GET pathway and its impact on transcript regulation had been shown previously in other eukaryotes (23,49).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, lack of the mammalian GET3 orthologs TRC40 (transmembrane domain recognition complex of 40 kDa) leads to embryo lethality in mice, complicating global physiological analyses (21). Nevertheless, a handful of recent studies have started to analyze individual physiological consequences of the GET pathway in vivo using tissue-specific knockout (KO) approaches and observed that its function is required for a diverse range of physiological processes, such as insulin secretion, auditory perception, and photoreceptor function, in animals (22)(23)(24). A high degree of evolutionary conservation is often assumed, and it has been recognized that some components of the GET pathway are present in Arabidopsis thaliana (25,26).…”
mentioning
confidence: 99%
“…These genes are regulated by XBP1s [24,25] and are correlated with Xbp1 mRNA splicing following glucose stimulation in beta cells [43]. A recent study showed that impaired Golgi-to-ER retrograde transport can induce beta cell ER stress [44]. Moreover, blockage of ER-to-Golgi protein trafficking causes accumulation of proteins in the ER and thus ER stress in beta cells chronically exposed to saturated fatty acids [21,22,45].…”
Section: Hypoxia Impairs Er-to-golgi Protein Trafficking In Beta Cellsmentioning
confidence: 99%